2010
DOI: 10.1260/0263-6174.28.10.847
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Acid Blue 129 from Aqueous Solutions onto Raw and Surfactant-Modified Bentonite: Application of Temperature-Dependent Forms of Adsorption Isotherms

Abstract: Modification of raw bentonite from Ponorogo, East Java, Indonesia by microwave irradiation using cetyltrimethylammonium bromide (CTAB) was studied. The adsorption capabilities of raw bentonite and its modified form were examined through their use in the removal of Acid Blue 129 from aqueous solution. The adsorption isotherm and kinetic experiments were conducted at four temperatures (25, 30, 40 and 50 ºC). The fitting of the corresponding experimental data was tested using the temperature-dependent forms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…From all the modified treatments, SDS-treated RH showed maximum U(VI) removal and was selected for further biosorption optimization studies. This finding is complimentary to the work of Chen et al [15], and Yesi et al [14] who reported an increase in sorption capacity of surfactant modified silkworm exuviae and Bentonite respectively.…”
Section: Effect Of Pre-treatmentssupporting
confidence: 90%
See 1 more Smart Citation
“…From all the modified treatments, SDS-treated RH showed maximum U(VI) removal and was selected for further biosorption optimization studies. This finding is complimentary to the work of Chen et al [15], and Yesi et al [14] who reported an increase in sorption capacity of surfactant modified silkworm exuviae and Bentonite respectively.…”
Section: Effect Of Pre-treatmentssupporting
confidence: 90%
“…Surfactant pre-treatment introduces lyophobic and lyophilic groups capable of adsorbing at the biosorbent surface:solution interface. The adsorption of heavy metals onto biomass from aqueous solution can be enhanced in the presence of surfactants due to reduced surface tension and increased wetting power [14]. From all the modified treatments, SDS-treated RH showed maximum U(VI) removal and was selected for further biosorption optimization studies.…”
Section: Effect Of Pre-treatmentsmentioning
confidence: 99%
“…As is seen in Table 5 the contact time for proposed method in comparison with all of the adsorbents are preferable and superior to the literature which show satisfactory removal performance for AB129 as compared to other reported adsorbents [46,47]. …”
Section: Resultsmentioning
confidence: 85%
“…The temperature dependence forms of several adsorption isotherm models are adopted to correlate adsorption equilibrium data. In our previous studies, these particular models have been successfully applied to evaluate the adsorption equilibrium data of several organic compounds onto organo-clay [6,7].…”
Section: Introductionmentioning
confidence: 99%